Positive psychology and students’ English-speaking performance: A correlational study of senior high school students - SopiaCika Shinta; YuliantoSlamet Wahyudi; AminahMimin (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
This study aims to determine the Correlation between Positive Psychology (PP) according to Gratitude and Self-Efficacy and Student Speaking Performance. Concrete understanding of main ideas and supporting details in the first semester of twelfth grade for senior high school students in the academic year 2023/2024. The researcher employed a correlation study as the research strategy to understand the correlation. The population is students from the XII MIPA 2 semester. First, a total selection of students from each class is conducted, providing a sample of 32 individuals for this research. Researchers obtain data by using questionnaires and speaking test interviews. The researcher analyzed and calculated the correlation using SPSS. The correlation level was determined to be 0.803, a strong positive correlation between both. The findings of this investigation indicate that students’ Positive Psychology (PP) in Speaking Performance in terms of literal understanding has a significant correlation. Considering these findings is recommended for teachers who carry out activities in class with various student characters.